Analysis Existing Conditions of Octopus (Octopus vulgaris) in Pandanan Beach, Malaka Village, North Lombok - Sahrul Alim; Muhammad Marzuki; Rusmin Nuryadi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Octopus fishing activities are increasingly being carried out by local fishermen making the variety of catches uncontrollable. It is feared that this diversity of catches will affect the biological condition of the octopus, which will lead to a decrease in the catch of fishermen. This study aims to: (1) determine growth patterns, body shape, age group, condition factors, spawning/maturity fit and catchability in octopus fisheries management, (2) biological dimensions of octopus fisheries management, and (3) identify attributes / lever indicators to increase the index value and sustainability status of the biological dimensions of octopus fisheries management. The results showed that the growth patterns of octopuses landed on Pandanan Beach, North Lombok Regency, were negative allometric with a b value of 2.1600. Meanwhile, octopus body shape is in the less flattened category with a condition factor (K) value of 1.85, with 2 age groups, namely the first age group with a length range of 24 cm - 48 cm and the second age group with a length range of 49 cm - 68 cm. Meanwhile, the number of octopuses worth catching was 238 which weighed > 320 grams, and 2 octopuses that were not yet fit to catch weighed < 320 grams. The sustainability status of octopus management from the biological dimension obtained a value of 52.34% with a fairly sustainable status. The attributes that need priority attention are stock enrichment and range collapse. Changes to these two attributes will affect the increase or decrease in the value of the biological dimension sustainability index.